LEVEL OF KNOWLEDGE, ATTITUDE, AND PRACTICE OF GOOD MANUFACTURING PRACTICES (GMP) IN CHICKEN SLAUGHTERHOUSES AND CHICKEN CUTTING PLACES IN DENPASAR - Naura Anindya; Romy Muhammad Dary Mufa; I Wayan Masa Tenaya (Buletin Veteriner Udayana, 2026)
Chicken meat is the most widely consumed animal-based food commodity in Indonesia, making product quality and safety important. Chicken Slaughterhouses and Chicken Cutting Places serve as critical units in producing chicken carcasses that meet the principles of Safe, Healthy, Intact, and Halal (ASUH). This study aimed to determine the level of knowledge, attitudes, and practices regarding the implementation of Good Manufacturing Practice (GMP) in Chicken Slaughterhouses and Chicken Cutting Places in Denpasar City. This study used an observational design and a quantitative approach. Sampling was conducted using purposive and snowball sampling techniques. Fourteen respondents, including owners and quality control managers, were interviewed for this study. Data were collected through structured interviews using questionnaires. The level of GMP knowledge showed that 42.8% of respondents were in the good category, while the overall level of knowledge was low. The GMP attitude level showed that 85.7% of respondents had a positive attitude toward GMP implementation. Meanwhile, the GMP practice level indicated that 50% of the respondents were in the low category. GMP knowledge in Chicken Slaughterhouses and Chicken Cutting Places showed variation but tended to remain low. Although respondents’ attitudes toward GMP were generally positive, this was not yet reflected in their practices, which remained suboptimal and below the standard. This condition indicates a gap between knowledge and attitude and the actual implementation of GMP in the field. The recommendations of this study include continuous socialization and further research with more diverse respondents to improve knowledge, attitudes, and GMP practices among food handlers.